1999
DOI: 10.1046/j.1365-2222.1999.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal microflora in allergic Estonian and Swedish 2‐year‐old children

Abstract: Differences in the indigenous intestinal flora might affect the development and priming of the immune system in early childhood, similar to what has been shown in rodents. The role of intestinal microflora in relation to the development of infant immunity and the possible consequences for allergic diseases later in life requires further study, particularly as it would be readily available for intervention as a means for primary prevention of allergy by the administration of probiotic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
547
6
28

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 815 publications
(596 citation statements)
references
References 21 publications
(24 reference statements)
15
547
6
28
Order By: Relevance
“…However, gram-positive bacteria that are not strictly anaerobic, such as lactobacilli, may also translocate (34). Since the composition of the gut flora of allergic children and the composition of the gut flora of nonallergic children have been observed to differ, gastrointestinal exposure to microbes may be significant for protection against allergy (9,10,12,27). However, it is still not clear how different groups or species of bacteria modulate the immune system of the host or activate various types of APCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, gram-positive bacteria that are not strictly anaerobic, such as lactobacilli, may also translocate (34). Since the composition of the gut flora of allergic children and the composition of the gut flora of nonallergic children have been observed to differ, gastrointestinal exposure to microbes may be significant for protection against allergy (9,10,12,27). However, it is still not clear how different groups or species of bacteria modulate the immune system of the host or activate various types of APCs.…”
Section: Discussionmentioning
confidence: 99%
“…Bjo¨rksten et al (102) examined further whether atopic diseases among children are associated with differences in their intestinal microflora in Estonia with a low and in Sweden with a high prevalence of atopy at the age of 2 years. They found that the atopic children in both countries were significantly less often colonized with lactobacilli as compared with the nonatopic children, and concluded that differences in the indigenous intestinal flora might affect the development and priming of the immune system in early life.…”
Section: Exposure To Commensals In the Gastrointestinal Tractmentioning
confidence: 99%
“…This hypothesis is supported by the observations of changes in the intestinal flora of atopic children, with a prevalence of clostridia [74,75]. In 2007, the first study was published postulating the role of probiotics in the recurrence of allergic respiratory symptoms in children.…”
Section: Allergic and Atopic Diseases In Childrenmentioning
confidence: 81%